Implementation Of Fixed-Term Work Agreements Based On Positive Law In Indonesia - Surya Perdana (DE LEGA LATA: JURNAL ILMU HUKUM, 2026)
An employment agreement, which is the beginning of an employment relationship, can be classified based on its duration. A temporary agreement can be referred to as a fixed-term employment agreement. A permanent agreement is called an indefinite-term employment agreement. A Fixed-Term Employment Agreement (PKWT) is an agreement between an employee and an employer when the parties agree to perform specific work within an employment relationship for a short period of time. Meanwhile, an Indefinite-Term Employment Agreement (PKWTT) is an agreement between an employee and an employer when the parties agree to perform work within an employment relationship for a continuous and fixed period of time. An employment agreement refers to contract law, which is an event in which one person promises to another or where two people mutually promise to carry out something. An agreement is considered valid if it meets the provisions stipulated in Article 1320 of the Civil Code. The requirements for a valid agreement are regulated in Article 1320 of the Civil Code. Article 1 Paragraph (14) of Law Number 13 of 2003 concerning employment states that an employment agreement is: "An agreement between a worker/laborer and an employer or employer containing the terms of employment, rights, and obligations of the parties." Employment agreements are divided into two types: PKWT and PKWTT. Provisions regarding written employment agreements are regulated in Article 54 paragraph 1 of Law Number 13 of 2003 concerning Employment. The provisions, nature, and type of work for fixed-term employment agreements can be seen in Article 59